Employer branding: elementos relevantes na intenção de permanecer: estudo exploratório com estagiários - Terrin, Simone Akemi (2015)
Attracting and retaining talent through inflated salaries can be expensive and not, necessarily, effective. Employer Branding (EB), which consists of the efforts of companies to promote features and attributes that make them attractive and desirable as employers, has gained attention of both companies and researchers of Human Resources and Management Practices. This exploratory study intended to identify which aspects of Employer Branding are most important for individuals intending to stay in a company after the probation period. The analysis contemplated 443 questionnaires distributed to large multinational financial institutions’ interns, using the employer's attractiveness scale, which considers five dimensions of Employer Branding (BERTHON; EWING; HAH, 2005): development, social, interest, application and economical. Statistical tests results demonstrated that demographic variables such as gender, type of college funding (public or private) and financial responsibility level influence the way individuals value each dimension. Although all dimensions have been considered relevant, logistic regressions considering the intention to stay show that, for the sample, economical issues stood out from the other variables. Finally, data analysis reveals aspects that can serve as input for readjustment of proposed speech and/or practices by companies willing to attract and retain, efficiently, interns for their workforce. In addition, the results of this research contribute to the theory when discussing existing categorizations for Employer Branding dimensions and suggesting that new classifications may be proposed by researchers.